2014
DOI: 10.1111/hiv.12140
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of adherence to antiretroviral therapy and HIV drug resistance over time in the Stratall ANRS 12110/ESTHER trial in Cameroon

Abstract: ObjectivesThe emergence of HIV drug resistance is a crucial issue in Africa, where second-line antiretroviral therapy (ART) is limited, expensive and complex. We assessed the association between adherence patterns and resistance emergence over time, using an adherence measure that distinguishes low adherence from treatment interruptions, in rural Cameroon. MethodsWe performed a cohort study among patients receiving nonnucleoside reverse transcriptase inhibitor (NNRTI)-based ART in nine district hospitals, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 35 publications
(59 reference statements)
1
42
1
Order By: Relevance
“…The findings of this study regarding patient groups at risk of ADRs are especially important in that they suggest a number of practical interventions that could be readily implemented in clinical practice to minimise patients' risk of developing ADRs. This would represent a significant advance in HIV/AIDS management in Ethiopia as our study demonstrated that severe ADRs were associated with not only self-reported non-adherence with therapy (the importance of optimal adherence to ART in BMI body mass index, ADR adverse drug reaction, OR odds ratio, CI confidence interval optimising patient outcomes is well-recognised [22,23]) but also a poorer patient outcome in terms of gain in BMI.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The findings of this study regarding patient groups at risk of ADRs are especially important in that they suggest a number of practical interventions that could be readily implemented in clinical practice to minimise patients' risk of developing ADRs. This would represent a significant advance in HIV/AIDS management in Ethiopia as our study demonstrated that severe ADRs were associated with not only self-reported non-adherence with therapy (the importance of optimal adherence to ART in BMI body mass index, ADR adverse drug reaction, OR odds ratio, CI confidence interval optimising patient outcomes is well-recognised [22,23]) but also a poorer patient outcome in terms of gain in BMI.…”
Section: Discussionmentioning
confidence: 79%
“…Patients who experienced severe ADRs were non-adherent, as reported in other studies [25,39], and experienced a lower increase in BMI. Early non-adherence to first-line regimens is associated with emergence of early and late regimen failure [22,40] and increasing treatment costs [41]. To our knowledge, no previous studies have reported that severe ADRs were associated with a decreased gain in BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Average adherence in each 3 month period for an individual is determined from the underlying tendency to adhere (which is a lifelong value for the individual, unless changed as a result of an adherence intervention) with within-person period-to-period variability (Fig 1) [6, 1524]. Each patient thus has a certain higher or lower tendency to adhere but their actual adherence varies over time, both at random and according to the presence of symptoms (with drug toxicity or presence of WHO stage 4 disease leading to a decrease in adherence) and age (tendency for increasing adherence with age).…”
Section: Methodsmentioning
confidence: 99%
“…Antiretroviral therapy has improved the health of many human immunodeficiency virus (HIV) positive individuals who otherwise would have died. Treatment efficacy relies, however, on sustained adherence, which constitutes a serious challenge to those receiving antiretroviral therapy [3]. The regimens are often complicated and can include varying dosing schedules, dietary restrictions, and adverse effects [4].Consistently high levels of adherence are necessary for reliable viral suppression [5] and prevention of resistance [6], disease progression, and death [7].…”
Section: Introductionmentioning
confidence: 99%